Sociological Correlates of Deviant Behaviour among In-School Adolescents in Lagos State, Nigeria - Emeri, Patience Nnenne (NIU Journal of Educational Research, 2025)
Where there is no law, there is no transgression is a popular saying but the human society is governed by series of laws through its various institutions. One of the hidden functions of education through its school agency is to instil conformity in learners for optimal societal functioning as law abiding citizens. Nonetheless, increasing number of adolescents are still bedevilled by social deviance. This study hence, examined the sociological correlates of deviant behaviour among secondary school students in Lagos state, Nigeria. Three hypotheses guided the study while   the study adopted a descriptive research design. The study sample comprised two hundred and seventy (270) secondary school students drawn from the study population using simple random sampling technique. A self-designed questionnaire (r = 0’76) was used in data collection while the formulated hypotheses were tested using regression analysis at 0.05 levels of significance. The study found that parental influence, social media and peer influence significantly predict deviant behaviour among secondary school students. The study hence, recommended among others that; Parents should provide a conducive home environment that would enhance good upbringing of their children and also be their role model. Parents should monitor the activities of their children and the kind of friends they keep, to discourage negative peer influence   Parents and the school system should regulate the contents of social media being accessed by adolescent students. Keywords: Deviant behaviour, Parental influence, Peer influence, Social media.